Complications and revision amputation following trauma-related lower limb loss. Issue 2 (February 2017) - Low, Eric Edison; Inkellis, Elizabeth; Morshed, Saam
Abstract: Introduction: Trauma-related amputations are a common cause of limb loss in the United States. Despite the military and public health impact of trauma-related amputations, distributions of various lower limb amputations and the relative frequency of complications and revision amputations have not been well described. We used the National Trauma Data Bank (NTDB) in order to investigate the epidemiology of trauma-related lower extremity amputations among civilians in U.S. trauma centers. Materials and methods: We conducted a secondary data analysis of the 2011–2012 NTDB research data sets, using means and frequencies to characterize the patient population and describe the distribution of major lower extremity amputations. Multivariable regression models were fit to identify predictors of major post-surgical complications, revision amputation, length of hospitalization, and in-hospital mortality. Results: A total of 2879 patients underwent a major lower extremity amputation secondary to a trauma-related lower limb injury, representing 0.18% of all NTDB trauma admissions from 2011 to 2012. 80.4% were male and 67.6% were white. The three most frequent definitive amputations preformed included trans-tibial (46%), trans-femoral (37.5%), and through foot (7.6%). The average length of hospitalization for all amputees was 22.7 days. Patients with at least one revision amputation stayed in the hospital approximately 5.5 days longer than patients not needing a revision amputation. 1204 patients (41.8%) required at least one revision amputation. 27.5% of amputees experienced at least one major post-surgical complication. African Americans experienced a 49% higher major post-surgical complication incidence and stayed, on average, 2.5 days longer in the hospital compared to whites. Injury severity score, age, hospital teaching status, presence of a crush injury, fracture location, presence of compartment syndrome, and experiencing a major post-surgical complication were all significant predictors of revision amputation. Conclusion: We report a high rate of complications and revision amputations among trauma-related lower limb amputees, and identify predictors of surgical outcomes that have not been described in the literature including African American race. Compartment syndrome is a significant predictor of major post-surgical complications, revision amputation, and length of hospitalization.